A Global Lethal Force Monitor: Comparative Opportunities and Challenges - Rappert, Brian (Homicide studies, 2023)
Comparison across jurisdictions is one way of assessing the appropriateness of lethal force resulting from the actions of law enforcement agencies. This article sets out a vision for a global use of force monitor that can enable meaningful comparisons between law enforcement agencies. It examines some of the opportunities and challenges associated with developing such a monitor in relation to (i) the legal frameworks in place governing use of lethal force; (ii) how official state agencies record and respond to deaths; and (iii) the contexts for the use of lethal force.